Carbon nanostructures for solar energy conversion schemes - Guldi, Dirk Michael; Sgobba, Vito (Chemical Communications, 2011)
Developing environmentally friendly, renewable energy is one of the challenges to society in the 21st century. One of the renewable energy technologies is solar energy conversion - a technology that directly converts daylight into electricity. This highlight surveys recent breakthroughs in the field of implementing carbon nanostructures - fullerenes (0D), carbon nanotubes (1D), carbon nanohorns, and graphene (2D) - into solar energy conversion schemes, that is, bulk heterojunction and dye-sensitized solar cells. © The Royal Society of Chemistry 2011.